Application of indocyanine green video angiography in surgical treatment of intracranial aneurysms - Felix Hendrik Pahl; Matheus Fernandes de Oliveira; Roger Schmidt Brock; José Erasmo Dal’Col Lucio (Arquivos de Neuro-Psiquiatria)
Indocyanine green (ICG) video angiography has been used for several medical indications in the last decades. It allows a real time evaluation of vascular structures during the surgery. This study describes the surgical results of a senior vascular neurosurgeon. We retrospectively searched our database for all aneurysm cases treated with the aid of intraoperative ICG from 2009 to 2014. A total of 61 aneurysms in 56 patients were surgically clipped using intraoperative ICG. Clip reposition after ICG happened in 2 patients (3.2%). Generally, highly variable clip adjustment rates of 2%–38% following ICG have been reported since the introduction of this imaging technique. The application of ICG in vascular neurosurgery is still an emerging challenge. It is an adjunctive strategy which facilitates aneurismal evaluation and treatment in experienced hands. Nevertheless, a qualified vascular neurosurgeon is still the most important component of a high quality work.